Comprehensive Assessment of Industries Economic Security: Regional Aspect - Akberdina, Viktoriya Viktorovna; Grebyonkin, Anatoliy Viktorovich; Smirnova, Olga Pavlovna (Economy of Regions, 2017)
The article investigates the interaction of the forms of network integration and the development of complimentary production networks in terms of economic security. Currently, the most developed countries are occurring a transition from the industrial society to the information society. The industry 4.0 as the continuous communication at all levels and characterizes the production processes, in which technologies and devices interact automatically in the value-added chain. Under these new conditions, the former types of organizational structures of economic entities are not sufficiently effective. Therefore, there is a need to create new, modern types of organizational structures. One of these types is network structures. Currently, they are becoming characteristic features of the new economy. Regional economic security depends on internal and external threats, which lead to unstable situations. Regional crisis situations are influenced by both macroeconomic crisis processes and local features of economic and social development, as well as the resource potential, geographical location, national and other peculiarities. The article defines the specific characteristics of the regions of the Ural Federal District, as well as the current situation of the regional economy and threats to the region. The authors have evaluated the economic security of complimentary production networks at the regional level. This evaluation has revealed the interconnection between complimentary production networks and the construction industry in the national economy. We have defined the economic security of complimentary production networks and specified the concept of complimentary production networks. The research findings may be applied by organizations as a new perspective of industry using network forms related to economic security.